Taxonomic assessment and historical context of Reichardia intermedia (Asteraceae) in the Canary Islands - Sicilia-Pasos, Guillermo; Arjona, Yurena; Padrón-Mederos, Miguel A.; Reyes-Betancort, J. Alfredo; García, Ángel; Jay-García, Louis S.; Tuero-Septién, Javier; Patiño, Jairo (Phytotaxa, 2024)
The Canary Islands harbor four species of the genus Reichardia according to the current knowledge. Three of them are endemic to the archipelago, one is widespread but probably also native. The discovery of a putative population of R. intermedia on La Gomera as a fifth Reichardia species triggered the revisiting of neglected historical occurrence reports of Reichardia for the Canarian archipelago. We combined phylogenetic and morphological evidence to confirm the identity of the newly discovered population and assessed the previous reports for the archipelago. Based on these findings, we confirm the presence of R. intermedia in the Canary Islands.